Experimental evaluation of analgesic property of bark skin of Saraca indica (Ashoka) and Shorea robusta (Shal) - Poonam S. Mohod, C. R. Jangde, S. D. Narnaware, Subhash Raut (Journal of Applied Pharmaceutical Science, 2014)
The aqueous and alcoholic extracts of bark skin of Saraca indica (Ashoka) and Shorea robusta (Shal) were evaluated for their analgesic activity in Swiss albino rats by making use of different pain models such as, tail immersion test, tail clip method and writhing induced by 4% NaCl solution. The aqueous and alcoholic extract of Saraca indica and Shorea robusta showed significant analgesic activity at 300 mg/ Kg body weight in Swiss albino rats as compared with control rats from physical, thermal and chemical stimulus of evaluation techniques. The analgesic activity might have been attributed to the presence of alkaloids, steroids in these plants as revealed from phytochemical analysis. On the basis of these observations it was concluded that Ashoka and Shal has got analgesic property, however further experimental as well as clinical evaluations are necessary.
Keywords: Saraca indica, Shorea robusta, Analgesic.